Chemotherapy refractory testicular germ cell tumor is associated with a variant in Armadillo Repeat gene deleted in Velco-Cardio-Facial syndrome (ARVCF) - Fung, Chunkit; Vaughn, David J.; Mitra, Nandita; Ciosek, Stephanie L.; Vardhanabhuti, Saran; Nathanson, Katherine L.; Kanetsky, Peter A. (Frontiers in Endocrinology, 2012)
Introduction: There is evidence that inherited genetic variation affects both testicular germ cell tumor (TGCT) treatment outcome and risks of late-complications arising from cisplatin-based chemotherapy. Using a candidate gene approach, we examined associations of three genes involved in the cisplatin metabolism pathway, GSTP1, COMT, and TPMT, with TGCT outcome and cisplatin-induced neurotoxicity. Material and Methods: Our study population includes a subset of patients (n=137) from a genome-wide association study at the University of Pennsylvania that evaluates inherited genetic susceptibility to TGCT. All patients in our study had at least one course of cisplatin-based chemotherapy with at least one year of follow up. A total of 90 markers in GSTP1, COMT and TPMT and their adjacent genomic regions (± 20 kb) were analyzed for associations with refractory TGCT after first course of chemotherapy, progression-free survival (PFS), overall survival (OS), peripheral neuropathy, and ototoxicity. Results: After adjustment for multiple comparisons, one SNP, rs2073743, in the flanking region (± 20 kb) of COMT was associated with refractory TGCT after initial chemotherapy. This SNP lies within the intron region of the Armadillo Repeat gene deleted in Velco-Cardio-Facial syndrome (ARVCF). The G allele of rs2073743 predisposed patients to refractory disease with a relative risk of 2.6 (95% CI 1.1, 6.3; P=0.03). Assuming recessive inheritance, patients with the GG genotype had 22.7 times higher risk (95% CI 3.3, 155.8; P=0.04) of developing refractory disease when compared to those with the GC or CC genotypes. We found no association of our candidate genes with peripheral neuropathy, ototoxicity, PFS and OS. Discussion: This is the first study to suggest that germline genetic variants of ARVCF may affect TGCT outcome. The result of this study is hypothesis generating and should be validated in future studies.